Quyu Shengxin Decoction Alleviates DSS-Induced Ulcerative Colitis in Mice by Suppressing RIP1/RIP3/NLRP3 Signalling. (21st August 2021) - Wu, Chuang; Yang, Haojie; Han, Changpeng; Wang, Qingming; Zhang, Haiyan; Huang, Ting; Mao, Wenjing; Tang, Cheng; Zhao, Wenjun; Zhu, Zhiming; Xu, Jing; Yang, Wei
Abstract : Purpose . To study the therapeutic effect of Quyu (QY) Shengxin (SX) decoction (QYSXD) in mice with dextran sulfate sodium- (DSS-) induced ulcerative colitis and to investigate the effects of QYSXD on the regulation of the receptor-interacting protein kinase 1 (RIP1)/receptor-interacting protein kinase 3 (RIP3)/nucleotide-binding oligomerization domain-like receptor family pyrin domain protein 3 (NLRP3) signaling pathway. Method . Thirty-six mice were randomly divided into the following 6 groups: the experimental group (QYSX group), the model group (DSS group), the positive control group (5-aminosalicylic acid (5-ASA) group), the control group, the first component group (QY group), and the second component group (SX group). Each group included 6 mice. Ulcerative colitis (UC) was induced in the mice by providing 3.5% DSS in drinking water. The mice were weighed every day to evaluate the disease activity index (DAI). After 7 days, the mice were sacrificed, and colonic tissues were obtained for colon length measurement. The morphological changes in the colon and the pathological scores of the mice in each group were observed by hematoxylin-eosin (HE) staining. The messenger ribonucleic acid (mRNA) and protein expression levels of RIP1, RIP3, dynamin-related protein 1 (Drp1), NLRP3, cysteinyl aspartate specific proteinase-1 (caspase-1), interleukin (IL)-1 β, and IL-18 in the colon tissues of the mice in each group were detected and compared by real-time quantitative reverse transcription PCR (RT-qPCR) and enzyme-linked immunosorbent assay (ELISA). The levels of RIP1, RIP3, NLRP3, IL-1 β, and IL-8 in the colonic mucosa were detected by ELISA. Western blotting was used to compare the protein expression of Drp1, caspase-1, mitochondrial fission protein 1 (FIS1), and mitophagy-associated protein light chain 3a/b (LC3a/b) among groups. The levels of reactive oxygen species (ROS) in the colonic mucosal cells were compared by immunofluorescence. Results . Compared with those in the DSS group, the mice with DSS-induced colitis in the QYSX group exhibited clearly higher body weights (P < 0.05 ) and DAI scores (P < 0.05 ). The colon lengths of the mice in the QYSX group were longer than those in the DSS group (P < 0.05 ), and the pathological score of the QYSX group was lower than that of the DSS group (P < 0.05 ). The RIP1, RIP3, Drp1, IL-1 β, IL-18, and caspase-1 mRNA levels in the QYSX, 5-ASA, SX, and QY groups were significantly lower than those in the DSS group (P < 0.05 ), but there were no differences between the QYSX group and the 5-ASA group. The levels of RIP1, RIP3, NLRP3, IL-1 β, and IL-18 in the QYSX group were lower than those in the DSS group (P < 0.01 ). The levels of Drp1, caspase-1, FIS1, and LC3a/b in the QYSX group and the 5-ASA group were lower than those in the DSS group (P < 0.05 ). The levels of ROS in the colonic mucosal cells in the QYSX, 5-ASA, and QY groups were lower than those in the DSS group (P < 0.05 ). Conclusion . QYSXD has certain therapeutic effects on DSS-induced colitis in mice and may be as effective as 5-ASA. QY and SX decoctions also have certain effects on colitis; however, these decoctions are not as beneficial as QYSXD. QYSXD may ameliorate colitis by inhibiting the expression of RIP1/RIP3/NLRP3 pathway-related proteins and reversing mitochondrial dysfunction to control inflammation.